2011
DOI: 10.1038/jhg.2011.75
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association analysis of TAP1 and TAP2 polymorphisms with aspirin exacerbated respiratory disease and its FEV1 decline

Abstract: Aspirin exacerbated respiratory disease (AERD) induces bronchoconstriction in asthmatic patients characterized with a clinical condition of severe decline in forced expiratory volume in one second (FEV1) after ingestion of aspirin. Two genes consisting a heterodimer, transporter 1 and 2, ATP-binding cassette, sub-family B (MDR/TAP) (TAP1 and TAP2) within the major histocompatibility complex (MHC) region, have been implicated in immunodeficiency and bronchiectasis development. To investigate the associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Subsequently, 126 articles were excluded due to duplication (n=24) or without relation to this topic (n=102). Following detailed evaluation of the remaining twelve studies, four studies were excluded with one being lack of relation to rs1057141 or rs1135216 polymorphism [ 15 ], one not being a case-control study [ 16 ], and two lack of enough pertinent data [ 8 , 14 ]. A total of 8 articles, with 7 published in English and 1 in Chinese, were included for qualitative synthesis based on the inclusion and exclusion criteria [ 5 – 7 , 9 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 126 articles were excluded due to duplication (n=24) or without relation to this topic (n=102). Following detailed evaluation of the remaining twelve studies, four studies were excluded with one being lack of relation to rs1057141 or rs1135216 polymorphism [ 15 ], one not being a case-control study [ 16 ], and two lack of enough pertinent data [ 8 , 14 ]. A total of 8 articles, with 7 published in English and 1 in Chinese, were included for qualitative synthesis based on the inclusion and exclusion criteria [ 5 – 7 , 9 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…As there are considerable variability and extensive LD throughout the HLA region, identification of causal variants for diseases within the HLA has remained difficult. We have already published an association of SNPs on TAP2, TAP1 [17], HLA-DPB1 [43], and WDR46 [44] with AERD in asthmatics. As seen in LD blocks between these genes (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
“…SNP of TAP1 was found to be associated with atopy [16]. In addition, we have found that SNPs and haplotypes of TAP1 and TAP2 are associated with aspirin-induced bronchospasm [17]. However, SNPs of the TAPBP gene have not been evaluated with respect to the development of AERD.…”
Section: Introductionmentioning
confidence: 95%
“…Unsurprisingly the strongest signal for asthma is found in the HLA with the lead signal specifically restricted to the HLA-DQA2 gene which has strong prior associations to asthma and hay fever all based on intergenic SNPs from multiple SNP based GWAS investigations (95)(96)(97)(98)(99). Some of our novel CNV associations for asthma (Supplementary Table 5) include signals in genes, TAP2 and STARD3NL, which have not been linked with asthma by previous SNP GWAS studies but have evidence of association to certain other respiratory diseases (100,101).…”
Section: Copy Number Variation Associations Testing In the Uk Biobankmentioning
confidence: 74%